Evidence for GTKO/β4GalNT2KO Pigs as the Preferred Organ-source for Old World Nonhuman Primates as a Preclinical Model of Xenotransplantation - Yehua Cui, MD; Takayuki Yamamoto, MD, PhD; Syed Sikandar Raza, BA; Mahmoud Morsi, MD; Huy Quoc Nguyen, BS; David Ayares, PhD; David K.C. Cooper, MD, PhD; Hidetaka Hara, MD, PhD (Transplantation Direct, 2020)
Background. Triple-knockout (TKO) pigs (in which expression of the 3 known pig carbohydrate xenoantigens has been deleted) are likely to be an optimal source of organs for transplantation into human recipients, many of whom do not have natural antibodies against TKO pig cells. However, old world monkeys, for example, baboons, have natural antibodies directed to TKO cells (to a “fourth” xenoantigen that is exposed after TKO). Methods. We measured (1) anti-pig IgM/IgG binding, and (2) complement-dependent cytotoxicity (CDC), by flow cytometry to α1,3-galactosyltransfearse gene-knockout (GTKO), GTKO/β4GalNT2KO (that do not express the “fourth” xenoantigen), and TKO pig peripheral blood mononuclear cells (PBMCs) using 72 baboon sera (30 specific pathogen-free [SPF], and 42 non-SPF baboons). Results. Mean IgM antibody binding to GTKO/β4GalNT2KO pig PBMCs was significantly lower than to GTKO or TKO pig PBMCs (P < 0.01). Mean IgG antibody binding to GTKO/β4GalNT2KO pig PBMCs was significantly lower than to TKO PBMCs (P < 0.01). Mean CDC of GTKO/β4GalNT2KO pig PBMCs was significantly lower than of GTKO or TKO pig PBMCs (P < 0.01). SPF baboon serum IgM and IgG binding to, and CDC of, GTKO/β4GalNT2KO or TKO PBMCs were significantly lower than non-SPF baboon sera (P < 0.01). Conclusions. Although TKO pigs form the basis for proposed clinical trials of xenotransplantation, it is difficult to identify baboons with a low or negative CDC to TKO pigs. For pig-to-baboon organ transplantation, the use of GTKO/β4GalNT2KO pigs would be preferable. The use of SPF baboons as recipients might be a minor advantage.